Reconstruction of Distal Radius GCT : A Case Report - Saputra, Rhyan Darma; Idulhaq, Mujaddid; Suko, Savero Iman Hari; Roshada, Musa Fasa (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Giant cell tumor (GCT) of distal radius poses problems for reconstruction following tumor resection. Reconstructive procedures such as vascularized and non-vascularized fibular graft, osteoarticular allograft, ceramic prosthesis, and mega prosthesis have been implanted for substitution of the defect in distal radius following resection. We described the outcome of distal radius GCT following wide resection and reconstruction with a locking plate and pedicle screw. CASE REPORT: A 35-years-old female came with a chief complaint of a painful lump in the right wrist for 8 months. Magnetic resonance imaging (MRI) showed the appearance of a cutaneous GCT, Campanacci 3. We performed wide resection and reconstruction with a locking plate and pedicle screw system. In 6 months follow-up, there was no significant pain, no sign of infection, and a functional range of movement, wrist extension 0–60°, wrist flexion 0–30°, and preserved hands movements. CONCLUSION: Reconstruction of distal radius GCT with a locking plate and pedicle screw system showed excellent functional outcomes. This method is a viable option as it provides good pain relief and functional improvement. However, the long-term outcome needs further evaluation.